FACTOR INFLUENCING GEN Z’S WILLINGNESS TO PAY FOR EVs: CLEAN ENERGY POLICIES IN MATARAM CITY - Devianur, Dinda; Hak, Muhammad Bai'ul; Arimbawa, I Wayan Agus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
Addressing climate change and promoting sustainable transportation, the use of electric vehicles (EVs) is considered an important step, especially in urban areas such as Mataram City. Conducting survey of 588 respondents for their technological prowess and environmental consciousness, investigates the factors influencing Generation Z's willingness to pay (WTP) for EVs and supporting policies. It looks at how socioeconomic status, technology use, environmental awareness, and mode of transportation affect WTP and intention to use using structural equation modeling (SEM). The findings support the Theory of Planned Behavior (TPB) by demonstrating that interest and WTP are significantly influenced by the mode of transportation and environmental awareness. In line with the Unified Theory of Acceptance and Use of Technology (UTAUT), technology use and socioeconomic status highlight the importance of environmental awareness while having less direct effects. Policies like tax breaks and subsidies for EV purchase. These findings can be supported by policies like tax breaks, subsidies for EV purchases, and investments in EV charging infrastructure. These observations help legislators encourage the use of EVs and sustainable urban growth.